Assessment Financial Distress of Islamic Banking in Indonesia Before and During Covid-19 - Syamsuddin, Mufidah; Hasan, Asyari (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2023)
This study aims to measure the level of financial distress of Islamic banking in Indonesia before and during Covid-19. The research method used is the Modified Altman Z-Score method. The sampling technique in this study used a purposive sampling technique so that there were 5 Islamic Commercial Banks as research samples, namely BCA Syariah, KB Bukopin Syariah, Bank Victoria Syariah, Bank Panin Dubai Syariah, and Bank Aladin Syariah. They use quarterly financial report data for the 2018-2019 research period (before covid-19) and 2020-2021 (during covid-19). The sampling technique used purposive sampling techniqueVariables in this study use variables from the Altman Z-Score analysis, namely WCTA, RETA, EBITTA, and BVEBVL variables. The results of this study indicate that during Covid-19, there were 3 Islamic Commercial Banks that were in a healthy condition or safe zone for two consecutive years, namely KB Bukopin Syariah, Bank Victoria Syariah, and Bank Aladin Syariah,2 Sharia Commercial Banks in distress zone and gray zone conditions namely BCA Syariah and Panin Dubai Syariah. In contrast, during covid-19, only two banks were in good health for two consecutive years, namely KB Bukopin Syariah and Bank Aladin Syariah. The other three banks are in a safe zone, gray zone, and distress zone, namely BCA Syariah, Bank Victoria Syariah, and Bank Panin Dubai Syariah.